FORMATION AND DISTRIBUTION OF NUCLEAR PORE COMPLEXES IN INTERPHASE - Maul, Gerd G. (The Rockefeller University Press, 1971)
The possibility of nuclear pore formation in the interphase nucleus was investigated in control and phytohemagglutinin (PHA) stimulated lymphocytes by the freeze-etching technique. 48 hr after the addition of PHA, the newly formed blasts which had not as yet divided had at least twice the number of pores per nucleus as controls. This clearly demonstrates that in lymphocytes nuclear pore formation can take place during interphase. It has generally been assumed that the distribution of nuclear pore complexes in somatic animal cells is random. However, we have utilized freeze etched rat kidney cells and a computer program to evaluate pore distribution. We find a minimum pore center-to-center spacing of approximately 1300 A and multiples thereof with high frequency. This is strong evidence for a nonrandom distribution of nuclear pores. The nonrandomness may be related to an underlying chromosomal organization in interphase. Using three criteria for identifying prospective pore sites (membrane specialization, nonrandomness, and alteration of heterochromatin distribution), we have found forming pores in sectioned material from cultured human melanoma cells. While nuclear pore formation may take place in conjunction with reformation of the nuclear membrane, a mechanism also exists for their formation during interphase.